Growth with equity : the new technology and agrarian change in Bengal - Dasgupta, Abhijit (New Delhi : Manohar Publishers & Distributors : Dhaka : University press, 1998)
With special reference to Nadia District, West Bengal, India, and Kushtia District, Bangladesh.
Includes bibliographical references (p. [167]-176) and index.
Keywords: Agriculture -- Economic aspects -- India -- West Bengal; Agriculture -- Economic aspects -- Bangladesh